Digital Ethics in the Utilization of Arabic Language Learning Applications: A Case Study at the State Islamic University of Sunan Ampel Surabaya/Etika Digital Dalam Penggunaan Aplikasi Pembelajaran Bahasa Arab: Studi Kasus Di UIN Sunan Ampel Surabaya - Nur Aqilah Lutfiya; Kamal Yusuf; Yusuf Abdurachman; Linura Tuada; Ilham Alauddin (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
This study aims to describe students’ understanding, practical implementation, supporting and inhibiting factors, and the implications of digital ethics in Arabic language learning at UIN Sunan Ampel Surabaya. Using a descriptive qualitative approach, data were collected through interviews, observations, and digital documentation involving 12 students and 3 lecturers who used platforms such as Zoom and Google Classroom. The findings indicate that students possess a strong understanding of digital ethics, which they associate with Islamic values such as adab, honesty, and responsibility. Their ethical awareness is reflected in polite communication, academic integrity, and attention to digital privacy. However, inconsistencies remain in practice, as minor plagiarism, limited participation, and reliance on digital conveniences are still observed. Supporting factors include moral awareness, lecturer role-modelling, and a religious academic environment, while inhibiting factors relate to limited digital literacy, academic pressure, and technical constraints. Overall, digital ethics significantly enhance the quality of Arabic language learning by fostering respectful interaction, academic integrity, and digital well-being.Penelitian ini bertujuan untuk mendeskripsikan pemahaman mahasiswa, praktik penerapan, faktor pendukung dan penghambat, serta implikasi etika digital dalam pembelajaran bahasa Arab di UIN Sunan Ampel Surabaya. Menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui wawancara, observasi, dan dokumentasi terhadap 12 mahasiswa dan 3 dosen pengampu mata kuliah bahasa Arab yang menggunakan aplikasi digital seperti Zoom dan Google Classroom. Hasil penelitian menunjukkan bahwa mahasiswa memiliki pemahaman etika digital yang baik dan mengaitkannya dengan nilai-nilai keislaman, terutama sopan santun komunikasi, kejujuran akademik, serta perlindungan privasi. Namun, penerapan etika digital belum sepenuhnya konsisten, ditandai dengan masih adanya plagiarisme ringan, partisipasi rendah, dan ketergantungan pada fasilitas digital. Faktor pendukung meliputi kesadaran moral, keteladanan dosen, dan budaya akademik religius, sedangkan hambatan utama berupa keterbatasan literasi digital dan kendala teknis. Etika digital terbukti berkontribusi pada peningkatan kualitas pembelajaran bahasa Arab.